Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702347
|View full text |Cite
|
Sign up to set email alerts
|

Statsplorer

Abstract: The difference between mouse and trackpad is significant Welch's t(20) = 2.39, p = .27… time technique The user selects variables of interest The user selects levels to compare Statsplorer shows suitable graphs Statsplorer automatically tests statistical assumptions and executes appropriate tests The user interprets the results The user learns about statistical analysis process Statsplorer visualizes the results Statsplorer generates report text 0 1 s m a ll m e d iu m la rg e 0.51 d Figure 1. Basic process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 30 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…This approach has been recommended for reporting statistical results in HCI over the traditional null hypothesis significance testing (with p-values only), which leads to dichotomous thinking [31]. It has seen increased use recently in HCI and visualization (e.g., see [17,30,42,69,74,79]).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been recommended for reporting statistical results in HCI over the traditional null hypothesis significance testing (with p-values only), which leads to dichotomous thinking [31]. It has seen increased use recently in HCI and visualization (e.g., see [17,30,42,69,74,79]).…”
Section: Resultsmentioning
confidence: 99%
“…There is an opportunity to better integrate preregistration into existing tools that aid the experimental design and analysis process in order to improve report quality. Interactive tools for experimental design and/or analysis (for example, TouchStone Mackay et al (2007), which aids in experimental design, or StatSplorer Wacharamanotham, Subramanian, Völkel, and Borchers (2015), which aids in analysis-even suggesting text to report a result in a paper), could have support for preregistration explicitly designed into them. Such a tool could aid a researcher in designing an experiment, preregistering that design, submitting that preregistration to an online registry, analyzing the results (while keeping track of any protocol deviations), and even give suggested text for writing up results with clear indications of what is exploratory/confirmatory and where protocol deviations occurred.…”
Section: Designing For Different User Roles Explicitlymentioning
confidence: 99%
“…Allowing users to control the content of a figure can improve their understanding (Wacharamanotham et al, 2015). Moreover, interactive figures might tackle issues of static illustrations such as hidden details (Weissgerber et al, 2016).…”
Section: Interactive Figuresmentioning
confidence: 99%
“…Similar to Jupyter, RMarkdown enables readers to change the code and to incorporate interactive figures (R Studio, 2017). Interactive figures are also automatically created by Statsplorer (Wacharamanotham et al, 2015) which supports students in understanding statistical tests. Adnan et al (2016) observed that even basic interactions, e.g.…”
Section: Interactive Figuresmentioning
confidence: 99%
See 1 more Smart Citation